The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1159/000101474
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Method for Quantifying the Output of Implantable Middle Ear Hearing Devices

Abstract: This report describes tests of a standard practice for quantifying the performance of implantable middle ear hearing devices (also known as implantable hearing aids). The standard and these tests were initiated by the Food and Drug Administration of the United States Government. The tests involved measurements on two hearing devices, one commercially available and the other home built, that were implanted into ears removed from human cadavers. The tests were conducted to investigate the utility of the practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
160
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(188 citation statements)
references
References 26 publications
(14 reference statements)
26
160
0
Order By: Relevance
“…They were somewhat below the mean of the reference data at frequencies above 700 Hz. This is in agreement with data for the ME transfer function of the investigated temporal bone, which also indicated a lower than average ASTM standard response [3], [43] at higher frequencies and consequently lower cochlear input. The corresponding phase of the transfer function is shown in Fig.…”
Section: B Intracochlear Sound Pressure Measurementssupporting
confidence: 91%
See 1 more Smart Citation
“…They were somewhat below the mean of the reference data at frequencies above 700 Hz. This is in agreement with data for the ME transfer function of the investigated temporal bone, which also indicated a lower than average ASTM standard response [3], [43] at higher frequencies and consequently lower cochlear input. The corresponding phase of the transfer function is shown in Fig.…”
Section: B Intracochlear Sound Pressure Measurementssupporting
confidence: 91%
“…Preparation of the human temporal bone for ICSP measurements followed a standard surgical approach [41], [42]. Prior to drilling access to the inner ear, a standard conformity test of the ME was performed by quantifying the TBME-01353-2016 6 ME transfer function and comparing it to the ASTM practice ME standards [3], [43]. The cochlear access (cochleostomy) to the scala tympani (ST, cf.…”
Section: Sensor Experiments In Human Temporal Bonesmentioning
confidence: 99%
“…It is unlikely that post-mortem changes in the EC or middle-ear acoustical properties affected our results, as the EC walls are effectively rigid in both live and cadaver adult ears, and comparisons of middle-ear acoustic (Rosowski et al, 1990) and mechanical properties in live subjects or patients (e.g., Goode et al, 1993;Chien et al, 2006Chien et al, , 2009Rosowski et al, 2007) have shown no appreciable post-mortem differences.…”
Section: Possible Effects Of Experimental Conditionsmentioning
confidence: 76%
“…The mechanical properties of the middle and inner ear were first confirmed by measuring the stapes and RW membrane velocities with acoustic stimulation from the external auditory canal via an appropriately calibrated insert earphone. The bones with acoustic stapes-velocity transfer functions outside the range described in the criteria by Rosowski et al [2007] were excluded. In all cases, the bony overhang of the RW niche was initially preserved.…”
Section: Temporal Bone Preparationmentioning
confidence: 99%
“…Our bone preparation allowed us to achieve LDV laser angles for stapes velocity measurements between 65° and 80° from the axis of piston-like stapes motion. The stapes and RW velocities were first measured with acoustic closed-field stimulation before driving the RW with an AMEI in order to confirm if the stapes and the RW velocities were in the normal range defined by Rosowski et al [2007]. Stapes velocity was again measured by stimulating the RW with the AMEI.…”
Section: Measurements Of Stapes Velocitymentioning
confidence: 99%